2016
DOI: 10.1097/bot.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Economic Impact of Generic Locking Plate Utilization at a Level II Trauma Center

Abstract: Therapeutic Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…Furthermore, a locking plate may cost more than a 1/4 tubular plate in many developing countries. 18 , 19 Therefore, fixation of first TMT joint fracture-dislocation using a 1/4 tubular plate is more suitable than using a locking plate with respect to both biomechanical and economical factors and can be widely used in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a locking plate may cost more than a 1/4 tubular plate in many developing countries. 18 , 19 Therefore, fixation of first TMT joint fracture-dislocation using a 1/4 tubular plate is more suitable than using a locking plate with respect to both biomechanical and economical factors and can be widely used in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…A study by McPhillamy et al explored use of generic implants compared to conventional implants in 828 patients. The hospital realized a 56% reduction in implant costs and $458,080 in total savings for the study period and clinical outcomes were equivalent [9] . A retrospective study in 2014 by Althausen et al [10] similarly showed no differences in clinical outcomes for patients with femoral neck fractures or posterior pelvic ring injuries managed with generic implants compared to conventional implants and a 70% reduction in implant costs was observed.…”
Section: Arguments In Favor Of Generic Implant Usagementioning
confidence: 94%
“…However, there have been well-documented cases of approved implants causing significant harm to patients. Although several studies have demonstrated the equivalence of quality between certain generic and brand name orthopedic implants, concerns regarding small put potentially harmful differences in manufacturing practices and the potential for disparate use of generic implants in economically disadvantaged patients raise ethical questions [9] , [10] . If generic orthopedic implants were found to have even a minor measurable negative impact on surgical outcomes, this would be a profound violation of the principles of nonmaleficence and the “difference principle” of justice, described by Rawls, that declares inequalities are only permitted if the conditions dictated ultimately benefit, not harm, the worst-off [20] .…”
Section: Arguments Against Generic Implant Usagementioning
confidence: 99%
See 2 more Smart Citations